EFFECTIVENESS OF GIBBERELLIC ACID TREATMENT AND SOAKING PERIOD ON SEED GERMINATION AND SEEDLINGS GROWTH OF " LOTUS" PERSIMMON ROOTSTOCK - Ayad T . Shayal Alalam; Ayad H. Alalaf; Nameer N.Fadhil (Mesopotamia Journal of Agriculture)
Seeds of " Lotus " kaki rootstock from mature fruits of 12 years old were used in this study where divided into 3 group . the first was soaked in water for 24. 48 and 72 hrs.. the second in GA3 at concentration 200 mg.l-1 for 24. 48 and72 hrs..and the third was soaked in GA3 at concentration 300 mg.l-1 for 24. 48 and72 hr.Seed were stratified in peatmoss and sand in the refrigerator at 5 c° for 100 days. At the end of stratification period. the seed were grown on the 30th of March 2011 in black polyethylene bags of 10kg. weight. Randomized complete block design was used with 2 factors and 3 replicates and 7 seeds for each treatment or replicates. The results given early of October/ 2011 indicted that water soaking of seeds for 72 hr.gave the highest seeds germination (90.47%). whereas. the lowest (47.61%) was from the seeds soaked for 48 hr. in 300 mg.l-1 GA3. Soaking the seeds in 200 mg.l-1GA3 for 24 hr. resulted in a significant increase of seedlings height and leaves number ( 68.15cm and 49.74 leaf). respectively. The highest diameter (5.40mm)resulted from the seeds soaked in water for 24hr. which were superior significantly on the seed soaked for 48 hr. in 300 mg.l-1 GA3 which gave the lowest diameter (3.40mm).